Effect of proton pump inhibitors and antibiotics on the gut microbiome of hospitalised older persons. Issue 4 (April 2016) - O'Donoghue, Caoilfhionn; Solomon, Katie; Fenelon, Lynda; Fitzpatrick, Fidelma; Kyne, Lorraine
Highlights: Clostridium difficile infection causes significant morbidity and mortality. Proton pump inhibitors have been associated with Clostridium difficile infection. We examined the effect of antibiotics and PPIs on the faecal microbiome. We found PPIs was associated with increased gut microbiome species diversity. PPIs appeared to attenuate the negative effects of antibiotics on the gut microbiome.